Estudio de factibilidad para la creación de una industria de confección y comercialización de camisas slim-fit para hombres en la ciudad de Loja - Ogoño Sinche, Robert Ernesto (2016)
This work corresponds to a result -oriented solution to " The lack of entrepreneurship in implementing shirt textile companies and industries in the City of Loja leading to mass consumption and reliance on imported and made in other cities study and thus leads to a flight of capital and undermines development prospects . "The research is part of determining the feasibility of creating a garment industry and marketing shirts Slim - Fit for women in the city of Loja. Which help to provide solutions to the problems of unemployment, migration and development, and contribute to the local market and the economy of our city, to the south and the country. Thus to achieve the intended objective of the present work was used office supplies and equipment as well as a methodology ( deductive and inductive method ) that was used to understand and analyze the information and thus present the results of our investigational work . The market survey through a sample of 380 surveys of 38,788 men between the ages of 15-35 years , the city of Loja ; procedure yielded information on the various demands , the average acquisition annually which is 7 shirts and this enabled determining the effective demand is then investigated using census at 44 dedicated to selling clothing companies (See Appendix No. 3) , registered in the CADECOL ( Loja Chamber of Commerce ) to set the offer. Regarding the Technical Study based on the previous study ( Market Research ) and according to the unmet demand is estimated to participate in the first year taking 31.03 % of the demand and in the tenth year the market will be covered in one 46.55 % . " INNOVATEX Co. : On regards the legal aspect, a limited liability company was formed . Ltd. "the company estimated useful life is 10 years from registration. In regards to the administrative study proposed that the company has the structural, positional and functional charts. In addition to operating manuals for each position so that the employee - worker perform effectively and efficiently. Deferred Assets amounting to a total of $ 4,110.00 united states of America ; , 6 investments in both the Financial Asset Studio to be $ 29,680.00 united states of America are then estimated and Actico Circulating Current or amounts to an amount of $ 15,554.55 from usa , giving a total required investment of $ 49,344.55 usa . Likewise, the total production cost for the first year is $ 189,398.16, and for the last year the production cost will be $ 318,054. While total revenue for the first year will be $ 231,000.00, for the last year of life of the project is estimated to get $ 492,677.00. With respect to net income with which to tell the company after taking their obligations to employees and tax - workers is as follows: for the first year will be $ 23,869.05 , and for the last year will get a net earnings of $ 102,469.63 . With regard to the balance point where costs are equal to income has the following data: for the first year must use the 68.44 % for the last year and you must use a 47.35 % of the production capacity ie he must make 7,525 shirts, with total sales of $ 157,040.21. Finally, the financial evaluation of the project was carried out based on the cash flows obtained for the ten year life of the project are: the first year is $ 31,130.77 and finally even the tenth year of life have a total project cash flow of $ 118,693.39 , based on which the financial evaluation indicators were applied but before that the MARR ( Minimum Profitable Acceptance rate ) which is 18.67 % for the mathematical calculation was obtained indicators , then applied to the NPV was $ 201,522.66 , pro value that determines that the project is financially feasible ; IRR of 72.75% which is higher than the MARR (18.67 %) was also used at much better performance in the cost of debt is generated , the PRC will be one year and ten months was also determined , also the RBC indicator , in which it was found that for every dollar invested in the project will be obtained is applied a profit of 36 cents. With respect to the indicator sensitivity analysis was applied to two scenarios , the first one is of higher costs with 21.28% to obtain a sensitivity coefficient of 0.9931 , that is less than one so therefore the project is not sensitive to the economic environment . The second is the decline in revenue with a 12.08% obtaining a sensitivity coefficient of 0.9936, i.e. is less than one so the project is not sensitive to this economic scenario. And finally to all information collected and analysis after the respective information 7 proceeds to the respective conclusions on which the studies conducted after it is concluded that the project is profitable and for this reason its implementation is feasible recommendations And finally they come to make recommendations such as being current on fashion trends , maintain and / or improve product quality and upgrade all the corporate image as increase sales or will be gaining ground in the market town of Loja